Academic performance of teaching assistants / trainners in engineering degrees (Ágora de Heterodoxias, 2018)
As it is known there are several teaching methodologies, including the Significant Learning Theory, which can be associated with the Dale Learning Pyramid, which consists of a model that describes how people learn and generate meaningful and lasting knowledge. In this model passive and active actions are considered, linked to the degree of depth of learning that the students obtain. Dale proposes that the level at which students can learn more, is where they perform actions linked to "teaching others", therefore, it follows that those students who perform tasks of assistants should obtain deeper learning. The questions asked to answer this work are: Is being an assistant/preparer implies a higher academic performance? And Is being an assistant/preparers generates oral communication skills? To answer this, the qualifications of 155 graduates of the civil engineering career of the PUCV were reviewed, some of whom had worked as assistant/preparers and others had not. With this information we found a fairly high positive correlation (academic performance, 0.9535 and oral presentation 0.8235), between the relative average of the students' scores with a certain number of assistants (with respect to the average of all) and the amount of assistantships that realized.
Keywords: teacher assistant; academic performance; learning pyramid; oral presentation; engineering students